Durability degradation simulation of RC structure based on gamma process considering two-dimensional chloride diffusion and life probabilistic prediction. (February 2023) - Zhang, Zhenhao; Ren, Xiaoxu; Niu, Qinglei; Zhang, Yi; Zhao, Bing
Abstract: In this paper, based on the gamma process, a new method for predicting the life of reinforced concrete (RC) structures eroded by chloride is presented considering two-dimensional (2D) chloride diffusion. First, according to the chloride diffusion theory, an analytical model and a finite difference numerical model considering 2D chloride diffusion under the action of multiple factors were established. Based on this, the Monte Carlo method and method proposed in this study were employed to predict the initial rust time of RC structures eroded by chloride. Histograms of the initial rust time and probability density function obtained using the two methods mentioned above were compared and analyzed to verify the validity of the proposed method. Finally, the life prediction model of the RC structure considering the initial rust time T 1, rust expansion cracking time T 2, and time when the concrete surface crack width reaches the limit crack width T 3 was established, and its applicability was verified through an analysis of an engineering example. The research indicates that the gamma process-based probability models can approximately predict the time required for rebar corrosion of an RC structure eroded by chloride considering 2D diffusion.